HUKUM SEBAGAI SISTEM NORMA - Diah Aju Wisnu W (Universitas Widya Gama Malang, 2018)
Talking about law as the system means that we are talking about law as a system of norm. As a system of norm, the creation of positive law should obey higher norms, so that a system of law is a leader of the principle of law pyramidally. Hopefully, referring to a law as a system of norm, the positive law may functional in the life of society.